Understanding the experience of initiating community-based group physical activity by people with serious mental illness: A systematic review using a meta-ethnographic approach. Issue 1 (22nd October 2020) - Quirk, Helen; Hock, Emma; Harrop, Deborah; Crank, Helen; Peckham, Emily; Traviss-Turner, Gemma; Machaczek, Katarzyna; Stubbs, Brendon; Horspool, Michelle; Weich, Scott; Copeland, Robert
Abstract: Background: People living with serious mental illness (SMI) experience debilitating symptoms that worsen their physical health and quality of life. Regular physical activity (PA) may bring symptomatic improvements and enhance wellbeing. When undertaken in community-based group settings, PA may yield additional benefits such as reduced isolation. Initiating PA can be difficult for people with SMI, so PA engagement is commonly low. Designing acceptable and effective PA programs requires a better understanding of the lived experiences of PA initiation among people with SMI. Methods: This systematic review of qualitative studies used the meta-ethnography approach by Noblit and Hare (1988). Electronic databases were searched from inception to November 2017. Eligible studies used qualitative methodology; involved adults (≥18 years) with schizophrenia, bipolar affective disorder, major depressive disorder, or psychosis; reported community-based group PA; and captured the experience of PA initiation, including key features of social support. Study selection and quality assessment were performed by four reviewers. Results: Sixteen studies were included in the review. We identified a "journey" that depicted a long sequence of phases involved in initiating PA. The journey demonstrated the thought processes, expectations, barriers, and support needs of people with SMI. In particular, social support from a trusted source played an important role in getting people to the activity, both physically and emotionally. Discussion: The journey illustrated that initiation of PA for people with SMI is a long complex transition. This complex process needs to be understood before ongoing participation in PA can be addressed. Registration—The review was registered on the International Prospective Register of Systematic Reviews (PROSPERO) on 22/03/2017 (registration number CRD42017059948).